Relações lineares, estratégias de manejo para o cultivo antecipado de trigo no Rio Grande do Sul - Moresco, Estéfano Antonio (2024)
Wheat cultivation has significant economic importance worldwide and is one of the most produced cereals in Brazil. The implementation of the early sowing system is an alternative to the cultivation system in the state of Rio Grande do Sul, providing cost reduction, diversification, and minimizing the risk of damage due to late frosts. The objective of this study was to evaluate the agronomic performance of wheat cultivars cultivated in early sowing in overseeding and row systems under a low-altitude subtropical environment. This study was conducted in Santa Maria - RS, in the 2023 agricultural year. The experiment included two systems, soybean overseeding and early row sowing, installed, respectively, on 03/16/2023 and 04/05/2023. The experimental design used was randomized blocks in a bifactorial scheme with three cultivars (ORS Feroz, ORS Guardião and ORS Senna) and five sowing densities (200, 300, 400, 500 and 600 m-²), and three replicates, totaling 90 experimental units. Sowing for the overseeding system occurred when the soybean crop was at the R7 phenology stage, totaling an area of 12 m². The row seeding anticipation system was carried out mechanized, with spacing of 20 cm, 3.4 m long and 1.8 m wide, totaling 6 m². Fertilization followed the technical recommendations of the crop. The variables evaluated were grain yield, hectoliter weight, spike length, number of spikelets per spike, number of grains per spike, thousand-grain weight, tillering dynamics and tiller survival index. The results indicate that there was a variation of 1.9 to 3.5 tillers in the overseeding system and of 0.9 to 1.5 for early row sowing. The tiller survival rate was not significant for both systems, suggesting a greater number than 9 plants evaluated per plot in future trials, increasing experimental precision. The increase in sowing density tended to reduce the presence of tillers, influencing grain yield. Pearson's linear correlations for the number of grains per spike and number of spikelets, regardless of the cultivar or sowing density, had positive correlations in the same direction, while for hectoliter weight and grain yield the tendency was to have negative correlations with the increase in sowing density. The overseeding system showed maximum technical efficiency for the cultivars ORS Feroz and ORS Guardião, respectively, 365.69 and 346 sem m-². In the early seeding system in rows, the maximum technical efficiency was found for the densities of 397.59, 476.34 and 451.03 sem m-² for the cultivars, respectively, ORS Feroz, ORS Guardião and ORS Senna. For the early seeding system in rows, higher seeding densities are necessary in relation to the overseeding system. The average productivity in the overseeding and row seeding systems were, respectively, 1,574.39 kg ha-1 and 2,021.08 kg ha-1. The viability of the systems depends on the technological level of the producer and the climatic conditions favorable to the cultivation.